Kajian Rekayasa Lalu Lintas Simpang TNI AU Rembiga Akibat Rekayasa Sistem Satu Arah pada Jl. Dr. Wahidin : Traffic Engineering Study of the TNI AU Intersection Rembiga Due to One Way System Engineering at Dr. Wahidin Street - Anwar Efendy; Titik Wahyuningsih; Nurul Hidayati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
TNI AU Rembiga intersection is a three-way link between the central point of Mataram city, which is also connected to the Rembiga intersection and the Dakota intersection, Rembiga. Dr. Wahidin street is an economic pathway for education, offices, and trade. At certain times, the traffic flow is very congested because the road is also the direction to West Lombok district. Based on observations at the research location, it was found that the distance between the Rembiga intersection and the TNI AU intersection was 322.8 meters which caused the movement of traffic flow to be less than optimal between the intersection distances so that it would affect performance at TNI AU intersection. For this reason, the purpose of this study was to examine the performance of the unsignalized intersection at the TNI AU Rembiga intersection due to the continued flow from the Rembiga intersection which is a signalized intersection due to a one-way system engineering carried out on the Dr. Wahidin street and before the implementation of the one-way system on the Dr. Wahidin street. This research was conducted with reference to the MKJI 1997, in which researchers conducted field observations, then collected primary data and secondary data. There is traffic flow engineering on Dr. Wahidin street, by creating a one-way system, had an impact on changing the performance of the unsignalized intersection at the TNI AU intersection to a level of service F with obstructed flow conditions, low speed whereas, before the implementation of the one-way system the level of service was E with stable flow conditions, stalled vehicles.